Aspek Pembiayaan Syariah Terhadap Profitabilitas Pada Bank Umum Syariah - Ratna Abdullah Abdullah (SEIKO : Journal of Management & Business, 2021)
Financing is still the most dominant activity in Islamic banks because it has an effect on profitability. Through financing efforts to improve the quality of productive assets can be realized. This study aims to examine the financing aspects, namely Musyarakah, Murabahah, Qardh and Ijarah that affect Profitability in Islamic Commercial Banks. Quantitative research using secondary data, namely the financial report data of 36-month Islamic Commercial Banks for the 2018-2020 period obtained from the Islamic banking statistics website. Data analysis used multiple linear regression which was processed through SPSS V.25. The results of the study found that a positive Musyarakah had no significant effect on profitability, while Qardh had a positive and significant effect on profitability. Meanwhile, Murabahah and Ijarah have a negative and significant effect on profitability.